Riverbank erosion displacees in Bangladesh: need for institutional response and policy intervention - Islam, MD Fakrul; Rashid, ANM Baslur (Bangladesh Journal of Bioethics, 2012)
Environmental refugees are one of the most burning issues at this time throughout the world. Bangladesh, a riverine country, is suffering from acquit riverbank erosion which compels millions of her population to be displaced from their place of origin. As such, 283 locations, 85 towns and growth centers, along with 2400 kilometers of riverbank line in Bangladesh are vulnerable to erosion. The major rivers e.g., the Padma, the Jamuna, and the Meghna, erode several thousand hectares of floodplain making thousands of people landless and homeless every year. Along with the floodplain, Bangladesh loses several kilometers of roads, railways, and flood-control embankments annually. No other disaster is as disastrous as riverbank erosion and ‘Internally Displaced Populations’ (IDP) face many unavoidable problems at different stages of displacement. Displacement marginalized them in respect of livelihood patterns and psycho-physical troubles. Such forty million homeless people in Bangladesh are compelled to lead a floating life. Riverbank erosion plays a major role in socio-environmental changes. The displaced people of riverbank erosion experience substantial socio-economic impoverishment and marginalization as a consequence of involuntary displacement from their original residence. Findings of a social survey carried out in 2008 on the erosion-hit displaced people in Chapai Nawabganj and Rajshahi districts are discussed in this paper. Newly settled people along with the native inhabitants have been interviewed to reveal the problems associated with making rearrangements for the displaced people. Besides these problems of displacement, adaptation strategies and relationships with the local people, their socioeconomic losses, sufferings, perception of natural disaster and psycho-physical problems, environmental ruins etc. have been revealed in this paper. There are no specific policies to rehabilitate the erosion-hit people. Thus, it is time to formulate policies to address prevention of riverbank erosion as well as to rehabilitate the river-erosion refugees. DOI: http://dx.doi.org/10.3329/bioethics.v2i2.9540 Bangladesh Journal of Bioethics 2011; 2(2): 4-19